2014
DOI: 10.5194/os-10-69-2014
|View full text |Cite
|
Sign up to set email alerts
|

The CO<sub>2</sub> system in the Mediterranean Sea: a basin wide perspective

Abstract: Abstract. The Mediterranean Sea (MedSea) is considered a "laboratory basin" being an ocean in miniature, suffering dramatic changes in its oceanographic and biogeochemical conditions derived from natural and anthropogenic forces. Moreover, the MedSea is prone to absorb and store anthropogenic carbon due to the particular CO 2 chemistry and the active overturning circulation. Despite this, water column CO 2 measurements covering the whole basin are scarce. This work aims to be a base-line for future studies abo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 75 publications
7
54
0
Order By: Relevance
“…The Mediterranean Sea is known to be highly supersaturated with respect to carbonate throughout the entire basin from the surface to depth (Álvarez et al, 2014;Schneider et al, 2010Schneider et al, , 2007. At the same time, it serves as a sink for anthropogenic CO 2 , which is absorbed in the surface layers and transported into the deeper parts of the basin through mixing (Ait-Ameur and Goyet, 2006;Bethoux et al, 2005).…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mediterranean Sea is known to be highly supersaturated with respect to carbonate throughout the entire basin from the surface to depth (Álvarez et al, 2014;Schneider et al, 2010Schneider et al, , 2007. At the same time, it serves as a sink for anthropogenic CO 2 , which is absorbed in the surface layers and transported into the deeper parts of the basin through mixing (Ait-Ameur and Goyet, 2006;Bethoux et al, 2005).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Coccolith calcification is expressed by coccolith weight and increases under conditions that are favorable for coccolithophore calcification. Therefore it is an indicator for the calcification rate of the coccolithophore cell (Bach et al, 2012). A global study on the variations of coccolith weight over the natural range of CO 2 concentrations in the world's oceans has shown that coccolith weight decreases with increasing CO 2 and this effect can also be traced back in sedimentary archives of the last glaciation under natural CO 2 variations (Beaufort et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the pH in the neighbouring North Atlantic Ocean decreased by just 0.0017 a −1 associated with an increase in c(DIC) of around 1.4 µmol kg −1 a −1 and a temperature rise of 0.01 • C a −1 (Bates et al, 2012). The greater potential of the Mediterranean Sea to store anthropogenic carbon can be explained by its higher alkalinity, warmer temperatures, and thus lower Revelle factor (Álvarez et al, 2014;Touratier and Goyet, 2011) when compared with other oceans, such as the North Atlantic.…”
Section: Introductionmentioning
confidence: 88%
“…The c(DIC) and A T were greatest at depths below 250 m with lower values seen closer to the surface (Fig. 5a-b), which is typical of the northwest Mediterranean Sea (Copin-Montégut and Bégovic, 2002;Álvarez et al, 2014). The higher values of A T and c(DIC) at depth and in the east support the notion that this is LIW, as this water mass has previously been identified as having an A T of around 2590 µmol kg −1 and a c(DIC) of roughly 2330 µmol kg −1 (Álvarez et al, 2014), coinciding with the warmer saltier waters.…”
Section: Ship-based Datamentioning
confidence: 99%
See 1 more Smart Citation